The impact of white turmeric rhizome extract on the histopathological characteristics of the pancreas in male wistar rats with diabetes - Lubis, Zahra Khairunnisa; Ongko, Nicolas Xavier; Soekardi, Adi; Razoki, Razoki (Buletin Kedokteran & Kesehatan Prima, 2025)
This study investigates the potential of white turmeric (Curcuma zedoaria Rosc.) rhizome extract as a cost-effective treatment for managing diabetes, focusing on its impact on pancreatic histopathology and blood glucose levels in diabetic Wistar rats. The research employed a randomized pre-test and post-test control group design, with rats induced with alloxan to simulate diabetes. The treatment groups received varying doses of white turmeric extract (250 mg/kg BW, 500 mg/kg BW, and 750 mg/kg BW) for 14 days. Histopathological analysis of the pancreas revealed that the white turmeric extract groups showed no signs of edema, inflammation, or necrosis, indicating a protective effect. Blood glucose level measurements demonstrated that the 500 mg/kg BW dose exhibited the most optimal results in lowering blood glucose levels. Statistical analysis using ANOVA and Kruskal-Wallis tests indicated significant differences between groups. These findings suggest that white turmeric extract, particularly at a dosage of 500 mg/kg BW, holds promise as a complementary treatment for managing diabetes by improving pancreatic health and reducing blood glucose levels. Further research is warranted to explore the underlying mechanisms and optimize its application.